2008
DOI: 10.1007/s10722-008-9338-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among different geographical groups, agro-morphology, fatty acid composition and RAPD marker diversity in Safflower (Carthamus tinctorius)

Abstract: Patterns of geographical diversity, and the relationship between agro-morphological traits and fatty acid composition were assessed for 193 safflower (Carthamus tinctorius) accessions representing forty countries. Accessions were assigned to eight groups based on geographical proximity. Cluster and Principal Component analyses were performed to assess patterns of diversity among the accessions and to select the most distant accessions from each of eight groups for analysis of randomly amplified polymorphic DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 25 publications
9
58
0
1
Order By: Relevance
“…Safavi et al, (2010), reported that 20 safflower accessions were separated into main 5 clusters with a cluster distance ranged from 0.27 to 0.85. Various others studies conducted by different investigators showed similar results such as Khan et al, (2009) and Mahasi et al, (2009). Safavi et al, (2010) and Amini et al, (2008) noticed similarity coefficient in the range of 0.26 to 0.57 and 0.30 to 0.89, respectively.…”
Section: Cluster Analysis Based On Rapd Datasupporting
confidence: 70%
See 1 more Smart Citation
“…Safavi et al, (2010), reported that 20 safflower accessions were separated into main 5 clusters with a cluster distance ranged from 0.27 to 0.85. Various others studies conducted by different investigators showed similar results such as Khan et al, (2009) and Mahasi et al, (2009). Safavi et al, (2010) and Amini et al, (2008) noticed similarity coefficient in the range of 0.26 to 0.57 and 0.30 to 0.89, respectively.…”
Section: Cluster Analysis Based On Rapd Datasupporting
confidence: 70%
“…81.08 % and noticed 3-9 RAPD fragments generated per primer with an average of 6bands per primer in safflower. Mahasi et al, (2009) and Khan et al, (2009) found out 61 and 78 amplified fragments from 14 and 15 RAPD primers and noticed 1-10 and 3-16 RAPD fragments generated per primer with an average of 5.5and 9.5 bands in safflower, respectively. On safflower same work was reported by Amini et al, (2008), and Souframanien and Gopalakrishna (2004) by using 15 and 25 RAPD primers which produced total polymorphic 132 and 44 bands and calculated amplified products range from 3 to 9 through standard of 1.8 and 13 bands for each primer, respectively.…”
Section: Rapd Analysismentioning
confidence: 99%
“…Safflower (Carthamus tinctorius L.), is a species that belongs to the Asteraceae family (Khan et al, 2009), is cultivated for many purposes. The oil extracted from its seeds has high levels of oleic and linoleic acids of excellent quality for human consumption and industrial use (Hamdan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The RAPD technique is a useful molecular method for genetic fingerprinting that requires only a small amount of DNA and random primers; sequence knowledge and the use of radioactive isotopes or hybridization protocols are not needed. In addition, the easy and fast application makes RAPD advantageous for molecular analyses (Khan et al, 2009). RAPD marker analysis is a suitable method to detect DNA alterations caused by radiation treatments.…”
Section: Discussionmentioning
confidence: 99%